‘Gezonde buitenlucht’ en ‘krachtige voeding’: kinderen en de anti-tuberculosecampagne in Nederland (ca. 1910–1940) - Bakker, Nelleke (Studium, 2013)
‘Healthy air’ and ‘powerful nutrition’: children and the anti-tuberculosis campaign in the Netherlands (c. 1910–1940)As elsewhere in the Western world, between 1910 and 1940 the anti-tuberculosis campaign in the Netherlands produced a wide range of initiatives to promote child health. In each of these the social and the medical were linked, as the hygienic ‘mood’ was encouraged by a child-saving ethos that focused upon the poor. In this article the author discusses from a comparative perspective the Dutch anti-tuberculosis interventions for children, the benefits projected on each of these, and the categories of children for whom they were meant. Private and voluntary initiatives dominated the field, whereas the state turned out to be very reluctant to take responsibility. Medically controlled health camps for weak children were a more important instrument than open-air schools and mass medical examination. Medical surveil- lance produced new categories and data which in turn justified the continued growth of child hygiene after tuberculosis had become less of a threat during the 1930s.